The Impacts of Genetic Counseling on The Quality of Children - Sjarif Hidajat Effendi (Indonesian Pediatric Society Publishing House, 2019)
The success of our National Family Planning Program and awareness of people to the motto of: "The norm of a small, happy and prosperous family" has led our people, especially the eligible couples, to think no more about quantity, but the quality of their children. There is a tendency that they do need assurance of completely healthy children, the present or the coming ones. This fact leads our Health Service Personnel to the awareness that they must be able to solve people's problems related to their desire for good quality children.